Eksplorasi Potensi Antibakteri Senyawa Xanton Dalam Garcinia mangostana L. : Review - Intan Khoirunnisa; Winasih Rachmawati; Elis Susilawati (Lumbung Farmasi: Jurnal Ilmu Kefarmasian, 2026)
Xanthone compounds are a group of secondary metabolites commonly found in Garcinia mangostana plants. Several studies have shown that the content of these compounds in mangosteen plants exhibits antibacterial activity against both Gram-positive and Gram-negative bacteria. This review aims to summarize various findings related to the antibacterial activity of mangosteen, both in extract form and pure xanthone compounds, as well as their mechanisms. A comprehensive literature search was conducted through PubMed, Mendeley, and Google Scholar databases using relevant keywords. Articles that met the inclusion criteria were reviewed to identify findings related to mangosteen's antibacterial activity. The results showed that several mangosteen extracts with different solvents, such as ethanol, methanol, and n-hexane, exhibited different metabolite profiles and activities against Gram-positive and Gram-negative bacteria, including Staphylococcus aureus, Escherichia coli, and Pseudomonas aeruginosa. Among the various xanthone compounds, α-mangostin is the most extensively studied and has shown potential antibacterial activity, although other xanthone metabolites may exhibit similar activity. The antibacterial mechanisms of this compound include membrane damage, increased permeability, and inhibition of biochemical pathways for growth. In conclusion, xanthone compounds have great potential as natural antibacterial candidates, but the exploration of specific metabolites is still limited to α-mangostin, highlighting the need for further exploration of xanthone metabolites and their relationship with antibacterial activity.